Topical perfluorodecalin resolves immediate whitening reactions and allows rapid effective multiple pass treatment of tattoos1. Issue 2 (19th December 2012) - Reddy, Kavitha K.; Brauer, Jeremy A.; Anolik, Robert; Bernstein, Leonard; Brightman, Lori; Hale, Elizabeth; Karen, Julie; Weiss, Elliot; Geronemus, Roy G.; Weiss, Robert A.; Geronemus, Roy G.
Abstract Background and Objective Laser tattoo removal using multiple passes per session, with each pass delivered after spontaneous resolution of whitening, improves tattoo fading in a 60‐minute treatment time. Our objective was to evaluate the safety and efficacy of topical perfluorodecalin (PFD) in facilitating rapid effective multiple‐pass tattoo removal. Study Design In a randomized, controlled study using Q‐switched ruby or Nd:YAG laser, 22 previously treated tattoos were treated with 3 passes using PFD to resolve whitening after each pass ("R0 method"). In previously untreated symmetric tattoos, seven were treated over half of the tattoo with the R20 method, and the opposite half with 4 passes using PFD (R0 method); two were treated over half with a single pass and the opposite half with 4 passes using PFD (R0 method); and six treated over half with a single pass followed by PFD and the opposite half with a single pass alone. Blinded dermatologists rated tattoo fading at 1–3 months. Optical coherence tomography (OCT) imaging of whitening was performed in two tattoos. Results Topical PFD clinically resolved immediate whitening reactions within a mean 5 seconds (range 3–10 seconds). Tattoos treated with the R0 method demonstrated excellent fading in an average total treatment time of 5 minutes. Tattoo areas treated with the R0 method demonstrated equal fading compared to the R20 method, and improved fading compared to a single pass method. OCT imaging of whitening demonstrated epidermal and dermal hyper‐reflective "bubbles" that dissipated until absent at 9–10 minutes after PFD application, and at 20 minutes without intervention. Conclusions Multiple‐pass tattoo removal using PFD to deliver rapid sequential passes (R0 method) appears equally effective as the R20 method, in a total treatment time averaging 5 minutes, and more effective than single pass treatment. OCT‐visualized whitening‐associated "bubbles, " upon treatment with PFD, resolve twice as rapidly as spontaneous resolution. Lasers Surg. Med. 45: 76–80, 2013. © 2012 Wiley Periodicals, Inc.